The correlation between patient satisfaction treatment of narrowband ultraviolet B phototherapy and the improvement of psoriasis severity index - Dewi, Putti Fatiharani (DiscoverSys Inc, 2021)
Background: Psoriasis is a chronic inflammatory disease of the skin affecting patients of all ages, both males and females. Currently, the psoriasis area and severity index (PASI) method is the gold standard in assessing the severity of psoriasis. Phototherapy narrowband ultraviolet B (NBUVB) is one of the modalities of psoriasis therapy which is relatively safe and effective for repairing psoriasis lesions. Patient satisfaction with phototherapy, which can be assessed using a questionnaire, serves to determine the patient's motivation in carrying out routine therapy.Objective: This study was designed to determine the correlation between the level of NBUVB phototherapy satisfaction with PASI improvement.Method: The study subjects were 22 plaque-type psoriasis vulgaris patients who underwent NBUVB phototherapy from May 2018 to October 2018 in the dermatovenereology outpatient clinic of Dr. Moewardi Hospital Surakarta. Subjects filled in the Treatment Satisfaction Questionnaire for Medication (TSQM) included questions about satisfaction with NBUVB phototherapy, and PASI scores were measured before and after NBUVB phototherapy.Results: The data were analyzed with the Pearson correlation test with a significance value of p <0.05. There are significant differences between PASI before and after giving 24 times phototherapy with a value of p<0.05.Conclusion: There was a significant correlation between the degree of PASI improvement and the global patient satisfaction with NBUVB phototherapy.